Impact of immunosuppressants on tumor pulmonary metastasis: new insight into transplantation for hepatocellular carcinoma - Jinyan Chen; Huigang Li; Jianyong Zhuo; Zuyuan Lin; Zhihang Hu; Chiyu He; Xiang Wu; Yiru Jin; Zhanyi Lin; Renyi Su; Yiyang Sun; Rongsen Wang; et al. (Cancer Biology & Medicine)
Pulmonary metastasis is a life-threatening complication for patients with hepatocellular carcinoma (HCC) undergoing liver transplantation (LT). In addition to the common mechanisms underlying tumor metastasis, another inevitable factor is that the application of immunosuppressive agents, including calcineurin inhibitors (CNIs) and rapamycin inhibitors (mTORis), after transplantation could influence tumor recurrence and metastasis. In recent years, several studies have reported that mTORis, unlike CNIs, have the capacity to modulate the tumorigenic landscape post-liver transplantation by targeting metastasis-initiating cells and reshaping the pulmonary microenvironment. Therefore, we focused on the effects of immunosuppressive agents on the lung metastatic microenvironment and how mTORis impact tumor growth in distant organs. This revelation has provided profound insights into transplant oncology, leading to a renewed understanding of the use of immunosuppressants after LT for HCC.